2015
DOI: 10.1016/j.jnucmat.2015.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability in thermally-aged CASS CF8 under heavy ion irradiation

Abstract: h i g h l i g h t sThermally-aged CF8 was irradiated with 1 MeV Kr ions at 400°C. Atom probe tomography revealed a strong dose dependence of G-phase precipitates.Phase separation of a and a 0 in ferrite was reduced after irradiation. a b s t r a c tThe stability of the microstructure of a cast austenitic stainless steel (CASS), before and after heavy ion irradiation, was investigated by atom probe tomography (APT). A CF8 ferrite-austenite duplex alloy was thermally aged at 400°C for 10,000 h. After this treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…M 23 C 6 carbides were located at the phase boundary. The precipitation of G-phase and α′ phase in ferrite in aged CF8 specimens was confirmed by the APT analysis in a companion study [24]. The G-phase precipitates with a mean size of 3 nm existed in the ferrite matrix, as shown in Fig.…”
Section: Microstructure Prior To Irradiationmentioning
confidence: 56%
See 1 more Smart Citation
“…M 23 C 6 carbides were located at the phase boundary. The precipitation of G-phase and α′ phase in ferrite in aged CF8 specimens was confirmed by the APT analysis in a companion study [24]. The G-phase precipitates with a mean size of 3 nm existed in the ferrite matrix, as shown in Fig.…”
Section: Microstructure Prior To Irradiationmentioning
confidence: 56%
“…The average size of TEM resolvable precipitates was 3.1 and 3.7 nm before and after irradiation. When the irradiation temperature increased to 350 and 400°C, the mean size of G-phase precipitates measured by TEM increased with increasing dose in the vicinity of M 23 C 6 carbides at the ferrite-austenite phase boundary, while G-phase precipitates measured by atom probe tomography (APT)[24] showed a size reduction (i.e. inverse coarsening) in the ferrite matrix away from the boundary.…”
mentioning
confidence: 99%
“…Similar 'inverse coarsening' behavior was first observed by Frost and Russell [53] due to the radiation induced ejection of solute atoms from the particles into the matrix, and diffusion of this solute back to and away from the particle. Li et al [54] reported that in thermally-aged CF8 steels irradiated with 1 MeV Kr ions, the size of the G-phase precipitates decreased while their density increased.…”
Section: Discussion: Stability Of Nos Under Irradiationmentioning
confidence: 99%
“…Among the family of stainless steels, cast austenitic stainless steels (CASSs) are preferably used in in water reactors as joints, primary circuit pipes, elbows, internals and valves due to their high mechanical properties and corrosion resistance [1][2][3][4][5][6]. These steels owe their properties to their microstructural features consisting of an austenitic matrix and δ-ferrite [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…These steels owe their properties to their microstructural features consisting of an austenitic matrix and δ-ferrite [3][4]. According to the literature, obtaining delta ferrite in solidified structure improves mechanical properties and corrosion resistance and minimizes the occurrence of hot cracks [1][2][3][4]. In most austenitic stainless steels, δ-ferrite forms as primary phase during solidification according to Ferrite-Austenite (FA) solidification sequence specified by Ni/Cr equivalent.…”
Section: Introductionmentioning
confidence: 99%